A two-stage model for development of antibody-producing cells - Cooper, M. D. (1972)
This model divides plasma cell differentiation into two developmental stages within the framework of the clonal selection theory. The first stage occurs within specific induction micro-environments, independently of foreign antigens, and involves the generation of multiple clones of B-lymphocytes from stem cells of haematogenous origin. During this stage, diversity of immunoglobulin classes is generated by an orderly intraclonal switch from IgM to IgG to IgA; the antibodies made are incorporated into the cell surface. The second stage occurs in the circulation and in peripheral lymphoid tissues; it involves clonal selection of B-lymphocytes by antigens with subsequent proliferation and differentiation to become either memory cells or antibody-producing plasma cells.